Sistema Web para el control y seguimiento de vacaciones, portafolio docente y administrativo para la Unidad de Talento Humano del Instituto Superior Tecnológico Babahoyo - Mariño, Keylla Liset (2021)
Today the implementation of a system which supports the execution of high demand processes has become a need that every public or private institution seeks to solve, since the imminent use of technology in all present areas It encourages the automation of specific processes, in order to obtain better results when it comes to wanting to manage said information. The Babahoyo Higher Technological Institute, through its Human Talent department, has found it necessary to find a technological solution to the constant inconveniences that arise when managing requests for teachers' portfolios and registered permits ; It is necessary through careful investigation to determine the processes that are managed to carry out these activities, and thus be able to generate their systematization. The objective of this work is to provide a technological solution to these requirements that for a long time have been carried out manually in office tools, forcing to have a lot of information that becomes a problem when classifying, even more so when It deals with the management of the calculation of vacation hours, where a series of regulations and parameters must be considered to deduct them or not from the registered permits. With all this, it remains to highlight the great management of the Babahoyo Higher Technological Institute to be able to recognize the positive impact that the systematization of specific processes brings and gradually integrate them into a single educational platform, which will be used as a general support tool.